Digitization of rare Balinese (Indonesia) Hindu ritual plants for conservation and biology education - I GEDE SUDIRGAYASA; SULISETIJONO SULISETIJONO; SUSRIYATI MAHANAL; ABDUL GOFUR; I KETUT SURATA; I MADE SUDIANA; I MADE MADURIANA (Society for Indonesian Biodiversity, 2025)
Abstract. Sudirgayasa IG, Sulisetijono, Mahanal S, Gofur A. 2025. Digitization of rare Balinese (Indonesia) Hindu ritual plants for conservation and biology education. Biodiversitas 26: 2735-2745. Plants hold significant philosophical and symbolic value in the ritual life of the Balinese Hindu community in Indonesia. Various plant species serve as essential components in religious ceremonies and are deeply rooted in local wisdom. However, modernization has led to the decline and fading recognition of some of these ritual plants among younger generations. This study, which adopts an interdisciplinary approach, aims to conserve, and revitalize ethnobotanical knowledge by exploring and digitizing rare Balinese Hindu ritual plants. Data were collected through field exploration, semi-structured interviews, and a literature review. The study successfully identified 56 rare plant species used in Balinese rituals. These species were digitized through a mobile and web-based platform called Taru Yadnya, which was also developed as a transdisciplinary biology learning medium grounded in local cultural wisdom. Digitization not only serves conservation purposes but also provides an innovative educational tool to facilitate knowledge transfer across generations. The results of this study are expected to contribute significantly to biodiversity preservation and cultural sustainability efforts in Bali while supporting transformative and contextual biology education.